A pilot study to assess oxidative and inflammatory markers as early indicator for response to chemotherapy in non‐small cell lung cancer. (23rd September 2019) - Diksha, Diksha; Gupta, Pooja; Malik, Prabhat Singh; Mohan, Anant
Abstract: What is known and objective: Oxidative stress and inflammation are known to be high in non‐small cell lung cancer (NSCLC). However, association of change in their levels with treatment response remains unaddressed. The present study evaluated change in blood levels of oxidative stress and inflammatory markers in NSCLC patients, after first course of platinum‐based chemotherapy. Methods: This prospective cohort study enrolled newly diagnosed NSCLC patients receiving either pemetrexed‐carboplatin (group A) or paclitaxel‐carboplatin (group B). Blood levels of malondialdehyde (MDA), reduced glutathione (GSH), interleukin‐6 (IL‐6), C‐reactive protein (CRP) and interleukin‐10 (IL‐10) were measured at baseline and after first cycle. Response to treatment was noted after 2nd or 4th cycle, as available. Subgroup analysis was done (group B), based on paclitaxel dose/formulation. Results: Of the 85 patients screened, 38 were enrolled with a mean age of 56.7 ± 9.2 years. Baseline levels of oxidative and inflammatory markers were not different between the groups and did not change significantly within the groups. Significant reduction in IL‐6 was seen with three‐weekly paclitaxel‐carboplatin (from median 81.3 [range 8.6, 1006] pg/mL to 51.8 [11.4, 99.5] pg/mL; P = .025). C‐reactive protein levels reduced with weekly nab‐paclitaxel ( P = .043). Change in levels did not relate with therapeutic response except for IL‐6 which decreased in patients with partial response (from 102.6 [8.1, 1006] pg/mL to 38.9 [8.4, 99.5] pg/mL; P = .036). What is new and conclusion: Although the levels of oxidative and inflammatory markers varied following chemotherapy, trend indicates that IL‐6 may be a potential marker of treatment response in NSCLC patients. Abstract : Markers of oxidative stress and inflammation were assessed in non‐small cell lung cancer (NSCLC) patients before treatment and after first cycle of chemotherapy. Significant decrease in IL‐6 levels in partial responders indicates that IL‐6 may be a potential marker of treatment response in NSCLC patients.